A multi‐proxy palaeoenvironmental and geochronological reconstruction of the Saalian‐Eemian‐Weichselian succession at Klein Klütz Höved, NE Germany. (15th May 2017) - Kenzler, Michael; Rother, Henrik; Hüneke, Heiko; Frenzel, Peter; Strahl, Jaqueline; Tsukamoto, Sumiko; Li, Yan; Meng, Stefan; Gallas, Julia; Frechen, Manfred
Abstract : Here we present a multi‐proxy investigation of the Klein Klütz Höved (KKH) coastal cliff section in northeastern Germany, involving lithofacies analysis, micromorphology, micropalaeontology, palynology and luminescence dating of quartz and feldspar. We subdivide the local stratigraphy into three depositional phases. (i) Following a Saalian advance (MIS 6) of the Scandinavian Ice Sheet, the penultimate deglaciation (Termination II) at the site occurred between c.  139 and 134 ka, leading to the establishment of a braided river system and lacustrine basins under arctic‐subarctic climate conditions. (ii) In the initial phase of the Eemian interglacial lacustrine deposits were formed, containing warm‐water ostracods and a pollen spectrum indicating gradual expansion of woodlands eventually containing thermophile deciduous forest elements. A correlation of the local pollen assemblages with Eemian reference records from central Europe suggests that fewer than 750 years of the last interglacial period are preserved at KKH. The occurrence of brackish ostracods dates the onset of the Eemian marine transgression at the section at c.  300–750 years after the beginning of the last interglacial period. (iii) Directly above the Eemian record a ~10‐m‐thick sedimentary succession of MIS 2 age was deposited, implying a significant hiatus of c.  90 ka encompassing the time from middle and upper MIS 5e to late MIS 3. During the Late Weichselian, KKH featured a depositional shift from (glacio‐)lacustrine to subglacial to recessional terminoglacial facies, with the first documented Weichselian ice advance post‐dating 20±2 ka. Overall, the KKH section represents an exceptional sedimentary archive for palaeoenvironmental reconstructions, covering the period from the Saalian glaciation and subsequent Termination II to the early Eemian and Late Weichselian. The results refine the existing palaeogeographical and geochronological models of the late Quaternary history in the southwestern Baltic Sea area and allow correlations with other reference records in a wider area.